Influence Analysis of Gojek Indonesia’s Corporate Social Responsibilty (CSR) on Corporate Image (Case of NGO “Yayasan Anak Bangsa Bisa”) - Larasati, Meuthya; Kartikawangi, Dorien (Archives of Business Research, 2024)
During the pandemic of 2020, Gojek Indonesia established a non-profit organization named Yayasan Anak Bangsa Bisa that aims to distribute aid and support to the stakeholders affected by the pandemic. This research seeks to discover if any influence is caused by implementing Gojek Indonesia’s Corporate Social Responsibility (CSR) on corporate image. The theories used in this research are the CSR Dimension Pyramid as the independent variable and Elements of Corporate Image as the dependent variable. The method used is descriptive quantitative, with a questionnaire as the chosen data collection method. This research concluded that there is a 40,2% positive influence between CSR implementation and Gojek Indonesia’s corporate image. Though the result is positive, Gojek Indonesia’s actions have not yet exceeded the public’s expectations. Gojek Indonesia’s overall corporate image is a trusted, innovative, and unique company. However, the corporate identity element, specifically the slogan ‘Pasti Ada Jalan,’ is still unfamiliar to the public. Thus, this research recommends that the following study consider the actions taken based on the existing corporate image and an interview with Gojek Indonesia’s team as an additional data collection method. A more practical recommendation is for Gojek Indonesia’s team to conduct social listening to observe the public’s expectations of CSR actions and add the slogan ‘Pasti Ada Jalan’ to their application and services layout.